Sonolytic, sonocatalytic and photocatalytic destruction of pharmaceuticals and personal care products in water - Savun, Başak. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
Pharmaceuticals and personal care products are used for health and cosmetic reasons and discharged readily to sewage treatment facilities to be transported to freshwater systems due to their low biodegradability. Ultrasound is an excellent tool for the destruction of such refractory chemicals, but the method is energy-intensive and ineffective for carbon-mineralization. Hence, combination of ultrasound with solid particles, or other processes (e.g. adsorption, homogeneous/heterogeneous AOP’s) is expected to improve the efficiency. The present study encompasses a thorough investigation of single ultrasound and combinations with adsorption, catalysis and photolysis for the destruction of PPCPs in water. The probe chemicals were salicylic acid, methylparaben and caffeine, while the catalysts were zero-valent iron (ZVI), sepiolite, TiO2, nanoparticles of sepiolite-SDS, and sepiolite-TiO2. The study also includes the use of an experimental design method for the analysis and evaluation of the operating parameters/factors, characterization of sonolytic and sonocatalytic systems, and determination of the individual and interaction effects of the operating parameters on the process efficiency. A summary of findings is as follows: i) ultrasound-assisted advanced Fenton reaction is much more effective than unassisted Fenton, via preventing H2O2 addition, which inhibits the mineralization process; ii) sepiolite is a good adsorbent and catalyst particularly when the surface is modified by sonication or when it is converted to a nanocomposite with sodium-dodecyl-sulfate (SDS); iii) Photocatalytic and sonocatalytic activity of TiO2 is significantly enhanced by modification of the catalyst surface to produce sepiolite/TiO2 nanoparticles.
Keywords: Hygiene products -- Environmental aspects.; Drugs -- Environmental aspects.; Sonochemistry.